2002
DOI: 10.1182/blood-2001-12-0353
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein targeting: a unique strategy to selectively eliminate immunoreactive T cells

Abstract: T lymphocytes have been found to harbor P-glycoprotein (Pgp) and to demonstrate modulation of its ion channel transporter function according to the state of activation of T lymphocytes. We hypothesized that cytotoxic chemicals that are extruded by Pgp could be used to specifically eliminate immunoreactive T-cell populations. In this study, we evaluated the capacity of 4,5-dibromorhodamine methyl ester (TH9402), a photosensitizer structurally similar to rhodamine, a dye transported by Pgp, and which becomes In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 73 publications
2
61
2
1
Order By: Relevance
“…33 The degree of allodepletion we achieved (Ն 1-2 logs) was similar to that obtained using immunotoxin-based purging or through ex vivo approaches designed to induce anergy of alloreactive T cells. 26,27,30,32 Consequently, we believe that standard apheresis products from healthy donors should yield sufficient quantities of alloreactivity-depleted T cells for clinical use, even if we assume that the precursor frequencies of alloreactive T cells in the haploidentical or mismatched setting may be significantly lower than those observed here. Given the demonstrated breadth of TCR diversity in the residual T-cell population following depletion of alloreactivity, relatively modest numbers of these cells (eg, 10 4 -10 6 /kg) might be sufficient to transfer meaningful infectious immunity without the need for prolonged cell sorting of the entire lymphoid fraction of an apheresis product.…”
contrasting
confidence: 44%
See 2 more Smart Citations
“…33 The degree of allodepletion we achieved (Ն 1-2 logs) was similar to that obtained using immunotoxin-based purging or through ex vivo approaches designed to induce anergy of alloreactive T cells. 26,27,30,32 Consequently, we believe that standard apheresis products from healthy donors should yield sufficient quantities of alloreactivity-depleted T cells for clinical use, even if we assume that the precursor frequencies of alloreactive T cells in the haploidentical or mismatched setting may be significantly lower than those observed here. Given the demonstrated breadth of TCR diversity in the residual T-cell population following depletion of alloreactivity, relatively modest numbers of these cells (eg, 10 4 -10 6 /kg) might be sufficient to transfer meaningful infectious immunity without the need for prolonged cell sorting of the entire lymphoid fraction of an apheresis product.…”
contrasting
confidence: 44%
“…Other investigators have developed alternate approaches to deplete [23][24][25][26][27][28][29][30][31] or anergize 32 alloreactive T cells. In one general strategy, cells expressing the CD25 antigen associated with the Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hMSC were grown in MSC growth medium (MSCGM) (Cambrex, Waskerville, MD, http://www.cambrex.com) and used at passages 2 through 9. The MSC phenotype was evaluated by direct immunofluorescence according to standard techniques [37,38], with monoclonal antibodies directed against the human antigens CD90, CD44, CD45, CD14, CD117, CD11b, CD34, CD38, CD33, CD32, CD10, CD64, CD71, CD13, and CD62L (Coulter Immunology, Beckman Coulter, Mississauga, ON, Canada, http:// www.beckmancoulter.com) (online supporting information Table 1). Immunofluorescence reactivity was determined by automated multiparameter flow cytometry analyzing a minimum of 10 4 cells (FACScan, Becton, Dickinson and Company, Mississauga, ON, Canada, http://www.bd.com).…”
Section: Cell Culture and Generation Of Conditioned Mediamentioning
confidence: 99%
“…This method demonstrated that alloreactive T cells were selectively eliminated, as anti-third party, anti-CMV T-cell responses and T-regulatory cell content were preserved in vitro in matched and mismatched pair MLRs. 10,11 When mice in an allogeneic BMT model were infused with photoallodepleted donor T cells, the GVL effect was preserved without GVHD. 12 In order to apply photodynamic purging of alloreactive T cells in the human haploidentical transplant setting, we investigated and reported a range of experimental conditions for optimal T-cell allodepletion with preservation of pathogen-specific responses and T-regulatory cells.…”
Section: Introductionmentioning
confidence: 99%